Complicated duodenal perforation in children: Role of T-tube - Rupesh Keshri; Digamber Chaubey; Ramdhani Yadav; Vijayendra Kumar; Vinit Kumar Thakur; Rashmi Ranjana; Sandip Kumar Rahul (Wolters Kluwer Medknow Publications, 2022)
Background: Diagnosis of duodenal perforation (DP) in children is often delayed. This worsens the clinical condition and complicates simple closure. Objectives: To explore the advantages of using T-tube in surgeries for DP in children. Patients and Methods: A retrospective study was conducted on all patients of DP managed in the Department of Paediatric surgery at a tertiary centre from January 2016 to December 2020. Clinical, operative and post-operative data were collected. Patients, with closure over a T-tube to ensure tension-free healing, were critically analysed. Results: A total of nine DP patients with ages ranging from 2 years to 9 years were managed. Five (55.6%) patients had blunt abdominal trauma; a 2-year-old male had perforation following accidental ingestion of lollypop-stick while a 3-year-old male had DP during endoscopic evaluation (iatrogenic) of bleeding duodenal ulcers; cause could not be found in other 2 (22.2%) patients. Of the five patients with blunt abdominal trauma, 4 (80%) had large perforation with oedematous bowel, necessitating repair over T-tube. Both patients with unknown causes had uneventful outcomes following primary repair with Graham's patch. Patients with lollypop-stick ingestion and iatrogenic perforation did well with repair over T-tube. The only trauma patient with primary repair leaked but subsequently had successful repair over a T-tube. One patient with complete transection of the third part of the duodenum and pancreatic injury who had repair over T-tube died due to secondary haemorrhage on the 10th post-operative day. Conclusion: Closure over a T-tube in DP, presenting late with oedematous bowel, ensures low pressure at the perforation site, forms a controlled fistula and promotes healing, thereby lessening post-operative complications.